Determination of design parameters of a biosensor for human artery pulse wave detection - Hasikin, K.; Ibrahim, F.; Soin, N. (2008)
This paper describes the modeling of a microdiaphragm of a human artery biosensor by varying diaphragm's diameter and thickness. Both parameters are varied to evaluate their effects on diaphragm's deflection and pressure sensitivity. The sensor used circular silicon nitride diaphragm as a pressure sensing element. The findings indicate that the diaphragm's thickness should be small whereas the diameter should be large enough in order to achieve high sensitivity. The simulation results demonstrate that the sensor has reasonable linearity and sensitivity for the measurement ranges from 0 to 300mmHg. Â© 2008 Springer-Verlag.